Pityriasis rosea and pityriasis rosea-like eruption after anti-SARS-CoV-2 vaccination: a report of five cases and review of the literature - Stefano Veraldi; Vinicio Boneschi; Marco Cusini; Carlo Alberto Maronese (PAGEPress Publications, 2022)
Only some cases of pityriasis rosea (PR)/pityriasis rosea-like eruption (PRLE) after anti-SARS-CoV-2 vaccination have been reported. In the period May 2021 - February 2022 we observed five cases of clinically typical PR that appeared 2 to 3 weeks after anti-SARS-CoV-2 vaccination with BNT162b2 (3 patients) or mRNA-1273 (2 patients). In four patients PR appeared after the first vaccination; in one patient after the second one. In three patients a biopsy for histopathological examinations was carried out. Results were typical for PR. In all patients laboratory examinations were within normal ranges. All patients were treated with cetirizine. Complete remission was observed within 14-30 days. Four patients were subjected to the second vaccination, but no skin lesions appeared. All patients are currently in good general health. It is possible that a relationship anti-Sars-CoV-2 vaccination−PR/PRLE exists; however, it is very rare, in consideration of millions of vaccinated subjects and the low number of reported cases of PR/PRLE. The pathogenesis of this relationship is unknown. However, some hypotheses may be advanced: PR/PRLE following anti-Sars-CoV-2 vaccination may be just a coincidence; anti-Sars-CoV-2 vaccines cause a reactivation of HHV-6 and/or HHV-7; vaccines can induce a delayed hypersensitivity response clinically similar to drug-induced PRLE.